Assessment of Confidence Levels of Undergraduate Senior Dental Students and Interns’ During Endodontic Treatment Procedures in a Sample From Saudi Arabia - Madfa AA; Almansour MI; Al‑Zubaidi SM; Almohefer SA; Alajlan SS; Alsaleh MK; Alanazi YA; Alajlan AS (Advances in Medical Education and Practice)
Ahmed A Madfa,1 Moazzy I Almansour,1 Saad M Al‑Zubaidi,1 Sami A Almohefer,1 Sarah S Alajlan,1 Mohammed K Alsaleh,1 Yosef A Alanazi,2 Abdalellah S Alajlan2 1Department of Restorative Dental Science, College of Dentistry, University of Ha’il, Ha’il, Kingdom of Saudi Arabia; 2Dental Student, College of Dentistry, University of Ha’il, Ha’il, Kingdom of Saudi ArabiaCorrespondence: Ahmed A Madfa, Department of Restorative Dental Science, College of Dentistry, University of Hail, Hail, Kingdom of Saudi Arabia, Tel +966165358200, Email ahmed_um_2011@yahoo.comBackground: The evaluation of students’ impression regarding their dental college experience is a crucial indicator of the effectiveness and achievement of dental education. The aim of this study is to evaluate the levels of confidence demonstrated by senior dental students and new interns during the execution of various endodontic treatment at College of Dentistry, University of Hail.Methods: A total of 76 senior students and 21 new interns at the University of Hail, Saudi Arabia, were administered anonymous surveys. Participants were instructed to assess their level of self-confidence using a Likert scale that spanned from 1 to 5. The statistical significance between the analysed groups was assessed using the Mann–Whitney U-test and the chi-squared test.Results: 63.9% of participants indicated their satisfaction with the quantity of teeth that were determined to require treatment. The majority of participants (91.8%) indicated that they believe their confidence in the field of endodontics will be strengthened by greater exposure to practical experience. Around 49.5% of the respondents indicated their intention to seek specialization in the future. Overall, the results of this study indicate that students and males tend to have lower levels of self-confidence in various endodontic procedures compared to interns and females (p < 0.05). A significant difference (p < 0.05) was noted in the levels of confidence between students and interns in treating various teeth. However, there were no statistically significant differences between the genders (p > 0.05). There were no statistically significant differences (p > 0.05) observed in the self-confidence levels related to the management of various indications between the two groups.Conclusion: The level of confidence pertaining to endodontic treatment among the participants is deemed satisfactory. The dental interns demonstrated a notable degree of self-assurance in executing root canal therapy, primarily attributable to their extensive engagement in clinical practice.Keywords: confidence, endodontics, education, dental students, self-assessment